The Implementation of Case-based Learning Approach in the Classroom: A Systematic Review - Shaynen Fatimah; Indah Juwita Sari; Jun S. Camara (Gagasan Pendidikan Indonesia, 2023)
This research aimed to see how the implementation of case-based learning approach in the classroom using systematic review method. Based on the analysis of 10 journal articles on the implementation of case-based learning approach in the classroom, it can be seen that the highest level of implementation is to measure student learning outcomes and students' critical thinking skills. While the least level of implementation of the case-based learning approach in the classroom is to measure science generic skills, learning activities, mathematical reasoning ability, and student learning motivation. Therefore, it can be concluded that the implementation of the case-based learning approach in the classroom has a good influence on improving students' 21st century abilities and or skills.